Bargaining Units and Bargaining Power - Forrest, Anne (Relations industrielles / Industrial Relations, 1986)
This paper examines how the recent amendment to the Labour Relations Actestablishing compulsory first contract arbitration in Ontario fits within the existing legal framework.